GESTION DES RESSOURCES NATURELLES CHEZ LES WE DE COTE D’IVOIRE : ARBITRAGE ENTRE EQUILIBRE AVEC LA NATURE ET TENSIONS SOCIOPOLITIQUES - Guiblehon, Bony (European Scientific Journal, ESJ, 2015)
This article highlights the contribution of “traditional” African societies to the modern environmental debate. It stresses the contribution of these societies in the understanding of environmental action in terms of management and protection of the living environment. For example, Among the Wè living in a forest area, there is a real concern of balance between man and nature. . They have a magical-religious view that drives them to ensure a balance with nature, because for them, the various orders that are made of the mineral, the animal, the plant and the human being are interdependent; a circulation force and energy occurs thereby between them.. This view is coupled with another one, or trans-historical heritage according to which man is part of nature, nature sheltering masks that are intermediaries between God and men. They are the ones that ensure the protection of natural resources and involved in the regulation of social order and social cohesion. But since the socio-political and military tensions in the country, management of natural resources is severely disrupted due to the illegal occupation of protected areas and their anarchic and illegal exploitation by armed individuals.